Increasing Student Learning Motivation through the Use of Interactive Digital Books Based on Project Based Learning (PjBL) - Liza Yulia Sari; Vivi Fitriani; Diana Susanti (Jurnal Penelitian Pendidikan IPA, 2022)
This research aims to increase student learning motivation through the use of interactive digital books based on project based learning. Biology learning strategy and design is one of the compulsory subjects that must be taken by students of the biology education study program at the University of PGRI West Sumatra and STKIP Ahlussunnah Bukititinggi. Based on observations made in the class of 2020 students who are taking biology learning strategy and design courses at the Biology Education Study Program at the University of PGRI West Sumatra and STKIP Ahlusunnah Bukittinggi, it was found the following problems, low student motivation in learning, this can be seen from students do not understand the explanation of the material presented by the lecturer, the students feel lazy when studying and do not want to read the material learned in the learning process and the boredom of students when listening to the lecturer explain the subject matter. One way that lecturers can do to increase learning motivation is to use digital books. So that with the digital book, students are expected to have the impetus or drive to carry out learning activities in higher education to achieve the learning goals they want. This research is descriptive qualitative research. The technique of collecting data is using a questionnaire, with 32 students as respondents. Based on the results of the study, it can be concluded that there is an increase in student learning motivation through the use of interactive digital books based on Project Based Learning (PjBL). The results are very high, namely 96.37%.